TAHAP DEFINISI DALAM FOUR-D MODEL PADA PENELITIAN RESEARCH & DEVELOPMENT (R&D) ALAT PERAGA EDUKASI ULAR TANGGA UNTUK MENINGKATKAN PENGETAHUAN SAINS DAN MATEMATIKA ANAK USIA 5-6 TAHUN - Birru Muqdamien; Umayah Umayah; Juhri Juhri; Desty Puji Raraswaty (Intersections, 2021)
Educational play tools (APE) have become a necessity during AUD learning because they are full of educational materials that can be adapted to their growth. This development research aims to produce a product in the form of a ladder snake APE in improving the cognitive abilities of children aged 5-6 years in the fields of science and mathematics at RA Mafatihul Ulum, Serang City, Banten Province. This type of research involves using a number of methods and types of research and going through various stages of research sessions, so each session is carried out to achieve its respective objectives. The Four-D Model development model suggested by Sivasailam This model consists of 4 development stages, namely; Define (defining), Design (Design), Develop (development) and Disseminate (deployment). The definition stage offered in the 4D model consists of several stages of analysis, namely curriculum analysis, needs analysis, student analysis, concept analysis, task analysis and formulation of learning objectives